“Nice White Meetings”: Unpacking Absurd Library Bureaucracy through a Critical Race Theory Lens - Nataraj, Lalitha; Hampton, Holly; Matlin, Talitha R.; Meulemans, Yvonne Nalani (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire)

(untitled) (Canadian Association of Professional Academic Librarians / Association Canadienne des Bibliothécaires en Enseignement Supérieur, 2020)
Although the issues of diversity and representation are often discussed within academic librarianship in Canada and the United States, the field has made little headway in being inclusive of the Black, Indigenous, and People of Color (BIPOC) who work within it. If academic libraries are to become truly authentic and inclusive spaces  where BIPOC are central not only to shaping the values of a library but also to determining how those values are accomplished, we must examine the traditional ways in which libraries function. One of these traditions is a reliance on bureaucracy and its associated practices such as structured group work and meetings, which are presumed to be inherently neutral and rational ways of working. Critical examinations of bureaucracy within higher education reveal how its overadoption is absurdly at odds with the social justice–oriented missions of most libraries. Furthermore, not all who are involved in libraries are equally harmed through this overreliance on bureaucracy; this article employs Critical Race Theory to uncover the insidious and specific deleterious impacts bureaucracies can have on BIPOC library workers. The antithesis of a neutral system, bureaucracy instead functions to force assimilation into a system entrenched in whiteness.